Specific epigenetic age acceleration patterns among four molecular subtypes of gastric cancer and their prognostic value - Zhou, Yu-Jie; Lu, Xiao-Fan; Meng, Jia-Lin; Wang, Qi-Wen; Chen, Jin-Nan; Zhang, Qing-Wei; Zheng, Kenneth I; Rocha, Claudia S; Martins, Carla B; Yan, Fang-Rong; Li, Xiao-Bo (Epigenomics, 2021)
To determine the association of the methylation age (Horvath epigenetic clock) of gastric cancer (GC) tissues with molecular subtypes and patient survival. Multivariate regression models were used to determine the association of methylation age acceleration (AA) with the clinical and molecular characteristics of 333 GC patients. Relative to the chromosomal instability subtype, the epigenetic AA was 49.8 (95% CI: 42.7–56.9) years for Epstein–Barr virus, 16.1 (10.6–21.6) years for microsatellite instability, and 6.05 (0.1–11.1) years for genomic stability subtype. GC patients with accelerated aging of tumor tissues had better outcomes (adjusted hazard ratio: 3.13; p = 0.03). Differentially methylated probes in patients with accelerated and decelerated methylation aging enriched in pathways including BMP signaling, HMGB1 signaling, STAT3 signaling and human embryonic stem cell pluripotency. Our results highlight the prognostic value of epigenetic AA in GC and suggest that epigenetic AA is also an indicator of molecular subtype in GC.